SIRT3: A New Regulator of Cardiovascular Diseases. (13th February 2018) - Sun, Wei; Liu, Caixia; Chen, Qiuhui; Liu, Ning; Yan, Youyou; Liu, Bin
Abstract : Cardiovascular diseases (CVDs) are the leading causes of death worldwide, and defects in mitochondrial function contribute largely to the occurrence of CVDs. Recent studies suggest that sirtuin 3 (SIRT3), the mitochondrial NAD + -dependent deacetylase, may regulate mitochondrial function and biosynthetic pathways such as glucose and fatty acid metabolism and the tricarboxylic acid (TCA) cycle, oxidative stress, and apoptosis by reversible protein lysine deacetylation. SIRT3 regulates glucose and lipid metabolism and maintains myocardial ATP levels, which protects the heart from metabolic disturbances. SIRT3 can also protect cardiomyocytes from oxidative stress-mediated cell damage and block the development of cardiac hypertrophy. Recent reports show that SIRT3 is involved in the protection of several heart diseases. This review discusses the progress in SIRT3-related research and the role of SIRT3 in the prevention and treatment of CVDs.